If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 144 = ((6 + x(2)) + x) * 2 Reorder the terms for easier multiplication: 144 = ((6 + 2x) + x) * 2 Remove parenthesis around (6 + 2x) 144 = (6 + 2x + x) * 2 Combine like terms: 2x + x = 3x 144 = (6 + 3x) * 2 Reorder the terms for easier multiplication: 144 = 2(6 + 3x) 144 = (6 * 2 + 3x * 2) 144 = (12 + 6x) Solving 144 = 12 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 144 + -6x = 12 + 6x + -6x Combine like terms: 6x + -6x = 0 144 + -6x = 12 + 0 144 + -6x = 12 Add '-144' to each side of the equation. 144 + -144 + -6x = 12 + -144 Combine like terms: 144 + -144 = 0 0 + -6x = 12 + -144 -6x = 12 + -144 Combine like terms: 12 + -144 = -132 -6x = -132 Divide each side by '-6'. x = 22 Simplifying x = 22
| 3(8-4x)=-120 | | 2(9+3x)=-18 | | 2x+5=6x | | 7x-40+7x^2=0 | | X^4+3x^3-11x^2+99x+8=0 | | -4k+17= | | 16t^2+24t+9=0 | | f+9.42=37.68 | | 5(b+1)=4(b+3) | | 8a+48= | | n^2+n-182=0 | | -9x-6=-4-10x | | y+.2=.4(y+5) | | 11-p=19 | | (2x^2-x-3)-(x+1)=y | | -5x+15=5 | | -2x=o | | (-5-6)+(-1-4)= | | 2(x-2)+2x=4(x+8)-36 | | 2(4y-3)-8=4+2y | | 6t+25=20-t | | .5m+2(.75m-1)=.25m+6 | | (2x^2-x-3)+(x+1)=y | | (6,4),(-5,-1)= | | 90=10p-99 | | x^2-2x+28=0 | | 3(3m+4)=6m-3 | | -1/2=y-1 | | 2x+x+2=169 | | .66b+2.97=.66b+2.97 | | .66b+2.97=.66+2.97 | | 3x+9=4x+4 |